Two-stage hybrid planning method for multi-satellite joint observation planning problem considering task splitting. (December 2022) - Song, Yanjie; Xing, Lining; Chen, Yingwu
Abstract: In recent years, the number of satellites in orbit has increased rapidly, which provides an effective guarantee for multiple satellites to complete earth observation missions jointly. In order to solve the multi-satellite joint observations planning problem(MSJOPP), a task splitting method is used to allocate tasks to satellites for execution effectively. Firstly, a mixed-integer programming(MIP) multi-satellite joint observation model is constructed, which fully considers the capabilities of resources for observing. After that, in order to plan these two types of tasks effectively, a two-stage hybrid planning algorithm(TSA) is proposed. TSA consists of an improved firework algorithm(FWA-I) and a heuristic algorithm(HA). In the first stage, FWA-I is used to process the inseparable observation task sequences. HA is used to plan the separable task sequences in the second stage. Finally, simulation experiments verify algorithms and the task splitting method. The task splitting method can effectively improve the performance of observation task planning. Highlights: Task splitting methods can improve the performance of satellite system. Improved fireworks algorithm can efficiently handle inseparable task sequences. Heuristic algorithm improves task completion rates through task splitting.